EXPERIMENTAL DETERMINATION OF ACTIVITIES OF FEO AND FE2O3 COMPONENTS IN HYDROUS SILICIC MELTS UNDER OXIDIZING CONDITIONS - Gaillard F.; Pichavant M.; Scaillet B. (My University, 2003)
The critical role of iron on crystal-silicate liquid relationships and melt differentiation is mainly controlled by the redox conditions prevailing in magmas, but the presently available database merely constrains the thermodynamic properties of iron-bearing components in strongly reduced and anhydrous molten silicate where iron is in the ferrous form. This paper provides new standard states for pure ferrous (FeOliq) and ferric (Fe2O3liq) molten iron oxides and extends the experimental database towards oxidizing and water-bearing domains. Iron-iridium, iron-platinum alloys, magnetite or hematite were equilibrated with synthetic silicic liquids at high temperature and high pressure under controlled oxygen fugacity (fO2) to determine activity-composition relationships for FeOliq and Fe2O3liq. Between 1000 and 1300°C, the fO2 ranges from that in air to 3-log units below that of the nickel-nickel oxide buffer (NNO). Experiments were performed on both anhydrous and hydrous melts containing up to 6-wt.% water. Incorporation of water under reducing conditions increases the activity coefficient of FeOliq but has an opposite effect on Fe2O3liq. As calcium is added to system, the effect of water becomes weaker and is inverted for Fe2O3liq. Under oxidizing conditions, water has a negligible effect on both activities of FeOliq and Fe2O3liq. In contrast, changes in redox conditions dominate the activity coefficients of both FeOliq and Fe2O3liq, which increase significantly with increasing fO2. The present results combined with the previous work provide a specific database on the energetics of iron in silicate melts that cover most of the condition prevailing in natural magmas.
Keywords: Silica melts